Team-Based Hospice Referrals: A Potential Quality Metric for Lung Cancer in the Immunotherapy Era. (January 2023) - Lycan, Thomas W.; Buckenheimer, Alyssa; Ruiz, Jimmy; Russell, Gregory; Dothard, Andy Shipe; Ahmed, Tamjeed; Grant, Stefan; Grey, Carl; Petty, William J.
Background: Immune checkpoint inhibitors (ICIs) can lead to durable responses in patients with lung cancer but may delay transitions to hospice at the end of life (EOL). We aimed to test the association of continuity of care with EOL outcomes in the ICI era. Methods: We collected retrospective data on all patients with lung cancer who started ICI treatment at a single comprehensive cancer center in the United States (1/1/14–5/1/18) and subsequently died. We defined a hospice referral as having continuity of care if placed by a provider from the patient's multidisciplinary cancer team (e.g., a medical oncologist, palliative care specialist, intensivist, and hospitalist). Results: In this cohort of 143 patients, 58% had a team-based hospice referral which was associated with a lower risk of death in the hospital. The most common reason patients declined hospice at EOL was an unwillingness to discontinue cancer-directed therapy. As compared to a similar historical cohort of patients treated with chemotherapy alone (2008–2010), there was a similar rate of hospice referral (68% vs 74%) but higher rates of new systemic therapy initiated within 30 days of death (17% vs 6%, p .001) and last dose within 14 days of death (13% vs 5%, p .005). Conclusions: Future studies should test the continuity of care at EOL as a new quality metric for advanced NSCLC.